Between development and surveillance: faculty perceptions and challenges of instructional coaching in an underdeveloped university context - Liu, Zhiming; Sulaiman, Tajularipin; Che Nawi, Nur Raihan (Frontiers in Education, 2025)
Although instructional coaching has been increasingly adopted as a tool for faculty professional development in Chinese higher education, it often encounters resistance due to signals of authority, emotionally detached delivery, lack of sustained follow-up, and non-specific or generic feedback. This qualitative study was carried out to explore how faculty at a public university in Gansu Province perceive the instructional coaching. To achieve that, the data collected through semi-structured interviews with 15 instructors from various disciplines and career stages were analyzed using thematic analysis, under a theoretical standpoint combining institutional theory with social constructivism. The findings revealed that faculty often perceived instructional coaching as a supervisory mechanism rather than developmental support, primarily due to ambiguous protocols, hierarchical feedback dynamics, limited disciplinary alignment, and emotionally distant communication. These conditions—rooted in institutional structure and interactional design—fostered anxiety, guarded engagement, and performative compliance, underscoring that faculty responses are shaped less by the idea of coaching itself and more by how it is enacted in context. Overall, the study suggests that faculty engagement with instructional coaching is shaped less by the model itself and more by how it is enacted—particularly in relation to trust, clarity, and relevance within a hierarchical context.